1996
DOI: 10.1177/44.8.8756756
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of L-selectin distribution on human leukocyte microvilli by immunogold labeling and electron microscopy.

Abstract: L-Selectin is a leukocyte cell adhesion receptor that contributes to neutrophil (PMN) rolling on activated endothelium at sites of idammation and mediates lymphocyte attachment to high endothelial venules in peripheral lymph nodes. Localization of this receptor to the tips of PMN and lymphocyte microvilli has been demonstrated. However, its distribution on these cells has not been quantified, and its localization on other leukocytes and the morphometry of microvilli on different leukocyte subpopulations have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
134
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 28 publications
9
134
0
Order By: Relevance
“…Immunogold labeling of L-selectin showed that the majority of L-selectin was enriched on microvilli ( Fig. S2B), as has been shown previously for endogenous L-selectin on numerous primary leukocytes (17). Endogenous CaM was coprecipitated with L-selectin-GFP from whole-cell lysates, demonstrating interaction with known binding partners (Fig.…”
Section: Polarized Shedding Of L-selectin Occurs In Primary Human Monsupporting
confidence: 78%
“…Immunogold labeling of L-selectin showed that the majority of L-selectin was enriched on microvilli ( Fig. S2B), as has been shown previously for endogenous L-selectin on numerous primary leukocytes (17). Endogenous CaM was coprecipitated with L-selectin-GFP from whole-cell lysates, demonstrating interaction with known binding partners (Fig.…”
Section: Polarized Shedding Of L-selectin Occurs In Primary Human Monsupporting
confidence: 78%
“…3A). Little or no L-selectin was detected on the rest of the plasmalemma of ␥␦ T cells, concurrent with the data previously reported for human leukocytes [20,21]. In contrast, WC1, a ␥␦ T cell subset marker, localized on the plasmalemma covering the ␥␦ T cell body but was absent on microvilli (Fig.…”
Section: Introductionsupporting
confidence: 89%
“…We also examined the expression of L-selectin on bovine lymphocytes to determine whether, as shown with human leukocytes [20,21], L-selectin is localized to the tips of microvilli. Lymphocytes were isolated as above, stained with DREG 56 (␣-L-selectin) or IL-A29 (␣-WC1) on ice, and visualized with goat anti-mouse IgG1 conjugated to 10 nM colloidal gold particles.…”
Section: Introductionmentioning
confidence: 99%
“…Human neutrophils, a type of leukocytes belonging to the innate immune system, have surface ruffles, called microvilli ( Figure 1A) [6,18], on which the sialomucin P-selectin glycoprotein ligand-1 (PSGL-1 or CD162) is expressed [33]. Most leukocyte rolling is mediated by PSGL-1 binding to P-selectin (CD62P) expressed on the inflammation-activated endothelium ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…The load-bearing PSGL-1-P-selectin bonds are responsible for the jerky "stop-start" motion seen in rolling. There is extensive prior literature on computational [4,7,8,17,[21][22][23][24]43,45] and experimental studies [6,25,26,29,30,35,42,44] of leukocyte rolling. However, the load-bearing bonds-that is, bonds that determine the leukocyte's rolling behavior-have not been rigorously identified and investigated.…”
Section: Introductionmentioning
confidence: 99%